TRAINING AND MENTORING ON PACKAGING OPTIMIZATION OF POLINEMA CRISPY DUWET BANANA GEDEBOG CHIPS IN THE COMMUNITY OF DUWET VILLAGE, TUMPANG SUB-DISTRICT, MALANG DISTRICT - Baroroh Lestari; Eny Widiyowati; Achmad Suyono; Becik Gati Anjari; Diana Eka Poernamawati; Cahyo Ramadhan Pratama (Transpublika Publisher, 2023)
This PKM/Service program aims to improve the packaging and promotion of